Achievements and Problems of Using Market Approaches in Modern Public Governance for Reforming Ukrainian State-Owned Corporations - Dunayev, Ihor; Gromov, Serhii (Pressing Problems of Public Administration, 2024)
The paper is devoted to the attempt of critical rethinking of the known achievements and problems of using market approaches in modern public governance for reforming Ukrainian state-owned corporations. The aim of the paper is to substantiate the perspective vector of state corporations reform based on the combined use of modern theoretical concepts of public governance, which directly provide for the adaptation of current market approaches of corporate governance to a more inclusive and value-oriented governance. The logic of the research is built on a chronological review of public administration concepts, starting from managerialization of the 1980s-1990s to modern approaches, such as “government as a platform” (GaaP), collaborative governance, and public value management. Such an approach allows tracing the evolution of theoretical foundations and practical applications in the field of public administration. The authors came to an important conclusion that the comparison of two perspective modern theoretical concepts (collaborative management of public policy and public value management) for the needs of modernization of large state corporations in Ukraine, these two approaches complement each other and can be applied in parallel. Collaborative management of public policy provides for the consideration of the interests of various groups at the policy formation stage regarding state corporations. And public value management focuses on the effective implementation of this policy at the operational level of state corporations in accordance with public values and interests. Therefore, the key task for Ukrainian reformers is to carefully balance the logic of the market and the principles of public administration in order to achieve a synergistic effect from their mutually complementary combination while preserving the priority of public values. The final conclusion is that for the successful reform of state corporations in Ukraine in 2024-2030, it will be necessary to apply the latest model of public policy management. This model should integrate the best achievements of previous concepts - flexibility and result-orientation from the “new public management” and good governance, horizontal networks and co-management with civil society, as well as a focus on public values from the concept of public value management.